Splitter plate application on the circular and square pin fin heat sinks. (July 2016) - Sajedi, R.; Osanloo, B.; Talati, F.; Taghilou, M.
Abstract: The main aim of this work is devoted to present a numerical analysis for studying effect of splitter on the hydro-thermal behavior of a pin fin heat sink. The concept of application of pins in the heat sinks arises from increasing the heat transfer area to reach maximum rate of heat losses in a limited space. On the other hand, flow separation behind the pin will enhance the pressure drop. To avoid or weaken the flow separation and reduce the pressure drop through the heat sink, a thin plate is located on the back of the pin. Two common pin fin heat sinks with circular and square pin shapes are compared together with and without splitters. Results showed that the use of splitter improves the hydro-thermal performance of both circular and square pins, so that the maximum improvement will be occurred for the case of Q  = 10 W and V  = 4.5 m/s. Results indicates that for circular pin fin heat sink with splitter pressure drop reduces by 13.4%, thermal resistance decreases by 36.8% and profit factor grows by 20%. Also for square pins the same results of 8.5% reduction for pressure drop, 23.8% reduction for thermal resistance and 14% increase in profit factor are observed. Also reliability analysis showed that for low-frequency and bipolar power transistor, the number of failure is reduced for circular and square splitter pin fin heat sinks. Highlights: This paper presents a new kind of heat sink using splitter behind pin fins. Splitter locating behind the pin-fin reduces thermal resistance and pressure drop. Splitters streamline the flow around the pins, so decrease driven power, the operation costs and energy consumption